Causal validation of the relationship between 35 blood and urine biomarkers and hyperthyroidism: a bidirectional Mendelian randomization study and meta-analysis - Xu, Wanxian; Wu, Jiao; Chen, Daolei; Zhang, Rui; Yang, Yue (Frontiers in Endocrinology, 2024)
Abstract Background Hyperthyroidism is an endocrine disorder with a relatively low global prevalence but significantly higher incidence among females compared to males. The onset age primarily ranges from 30 to 50, although it is not limited to this age group. Challenges in the treatment of hyperthyroidism include individualized treatment plan formulation, management of side effects, and prediction of disease progression, necessitating comprehensive consideration to achieve more effective therapy and management. Mendelian randomization studies can reveal more precise therapeutic targets between blood and urine biomarkers and hyperthyroidism, providing more decadent treatment options for the condition. Methods The study will build upon the omics Mendelian randomization (MR) framework by conducting MR analysis using 35 blood and urine biomarkers separately for two distinct databases of hyperthyroidism. Subsequently, the results will undergo meta-analysis and multiple corrections to ensure accuracy and reliability. Finally, positive findings will undergo reverse MR validation to verify causal relationships with hyperthyroidism. Results In the British database, the MR analysis of Total bilirubin levels about hyperthyroidism yielded an odds ratio (OR) of 1.097 (95% CI: 0.951-1.265, P = 0.205). Conversely, in the Thyroid Omics Association database, the MR analysis revealed an OR of 1.283 (95% CI: 1.122-1.467, P = 0.0002) for the same relationship. Meta-analysis of the MR analysis results from both databases, following multiple corrections, resulted in an OR of 1.192 (95% CI: 1.081-1.314, P = 0.015). Additionally, the direction of beta values in the MR analysis results from both databases was consistent. Conclusions The urine biomarker total bilirubin levels may contribute to an increased risk of hyperthyroidism and accelerate its progression, thus representing a risk factor for the condition.